Lower crust structures and dynamics of southern California revealed by first P and PmP traveltime data - Wu, Shucheng (2022)
The lower crust plays an important role in coupling the upper mantle force to the brittle upper crust at transform plate boundary regions. Yet, the tomographic resolution in the lower crust is typically much lower than the upper crust, given that most earthquakes take place at seismogenic depths. Here, we present a new P-wave velocity model of the entire crust in southern California by jointly inverting arrival times of first P and Moho reflected PmP waves. A total of 29,512 robust PmP arrivals are picked by a new semi-automatic workflow, forming the largest earthquake-sourced PmP dataset in southern California to date. Such abundant PmP arrivals remarkably improve the resolution of middle and lower crust in tomographic imaging. Our final velocity model reveals prominent low-velocity anomalies beneath the Eastern California Shear Zone (ECSZ) and south of the Coso Volcanic Field (CVF) in the lower crust. We attribute the low velocities beneath the ECSZ to deep fluid concentration which not only triggers major crustal earthquakes but may also contribute to the long-term development of the shear zone. While the low-velocity anomaly south of the CVF may imply the deep magma source of the CVF is located to its south.